Measuring sectoral patterns of US investment in EU member countries, 1983 - 1994 - Holger Görg; Frances P. Ruane (Trinity College, Department of Economics, 1997)
This paper analyses the sectoral distribution of US investment across EU member countries. We attempt to determine whether investment is sectorally concentrated by country and whether there seems to be any evidence of increased sectoral specialisation in US investment as the EU market has become more integrated. Our empirical results indicate that US investment is relatively sectorally concentrated by country and that there has been some slight increase in specialisation in mainly small and peripheral member countries, while in most of the large core EU countries, no increase in specialisation is evident. (3,564 words)
Keywords: F21; F23; 330; Direktinvestition; Wirtschaftsstruktur; Messung; USA; EU-Staaten